Active equity management - Zhou, Xinfeng; Jain, Sameer (Not identified Not identified, 2014)
Active Equity Management provides a comprehensive understanding of technical, fundamental, and economic signals used in equities trading. It explores in detail how such signals may be created, rigorously tested and successfully implemented. Filled with practitioner insights derived from years of experience in the hedge fund industry, and supported with academic theory, Active Equity Management provides an in-depth review of basic financial concepts, examines data sources useful for equities trading, and delves into popular seasonal effects and market indicators. It also highlights best practices in model development, portfolio construction, risk management, and execution. In combining topical thinking with the latest trends, research, and quantitative frameworks, Active Equity Management will help both the novice and the veteran practitioner understand the exciting world of equities trading. -Covers extensive data sources to build investing information, insight and conviction edges -Examines seasonal effects, explores economic & market indicators to make better trading decisions -Addresses technical and fundamental signal construction and testing -Explains dynamic factor timing strategies, portfolio construction and management - Reviews standard approaches for trade-level and portfolio-level performance measurement -Discusses implementation, trading cost analysis and turnover management
Includes bibliographical references and index.
oif 17/12/2019
Loans
Keywords: Investment analysis; Stocks; Portfolio management